PHYSICAL AND MATHEMATICAL MODELING OF THE AERATION ZONE PROCESSES FROM CONTAMINATION - Biliaiev, M. M.; Kalashnikov, I. V. (Science and Transport Progress, 2008)
A numerical model to calculate the process of soil protection from pollution with the use of neutralizator has been proposed. The model is based on the equations of admixture transfer. The results of numerical and physical experiments are presented.